Defect engineering in trivalent ion doped ceria through vanadium assisted charge compensation: insight using photoluminescence, positron annihilation and electron spin resonance spectroscopy. Issue 46 (18th November 2021) - Das, Debarati; Gupta, Santosh K.; Mohapatra, M.; Sudarshan, K.
Abstract : This work highlighted the strategy to demonstrate the appearance↔disappearance of VO in ceria by choice of the dopant and co-dopant and their relevance in need based defect related applications. Abstract : Pair matching charge compensation with trivalent and pentavalent dopants in ceria was found to be an attractive strategy in engineering defects with minimal distortions in the lattice and obtaining enhanced catalytic properties. In the present study, charge compensation with a vanadium codopant in trivalent ion doped ceria is studied. Defect evolution in the trivalent ion doped ceria with vanadium codoping has been studied in CeO2 :Eu 3+, CeO2 :La 3+, Eu 3+ and CeO2 :Y 3+, Eu 3+ systems and the choices of the dopant and co-dopant are triggered by their ionic radius. Eu 3+ photoluminescence (PL) is used as a spectroscopic probe to monitor local structural changes around the dopants. Positron lifetime studies showed that oxygen vacancies formed due to trivalent ion doping are weakly associated when larger ions are doped and result in the formation of vacancy aggregates. Positron lifetime studies along with XRD studies show that vanadium codoping effectively removes the vacancies but the distortions are significant when the size mismatch between the pair match used for charge compensation is higher. Photoluminescence demonstrated that the oxygen vacancies associated with Eu are more effectively removed in the case of Y codoped samples. Electron Spin Resonance (ESR) studies suggested that vanadium in excess over the stoichiometric concentration of the trivalent ion can lead to additional defects. These studies are expected to help in tuning the vacancy concentrations as well as controlling the lattice distortions for technological applications such as catalysis, ionic conductivity, etc .